1993
DOI: 10.1038/ki.1993.256
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair and recovery of RNA synthesis in uremic patients

Abstract: A high frequency of cancer appears among uremic patients. As depressed DNA repair ability is thought to be one of the causes for malignancy in cancer prone diseases, the present study was undertaken to examine DNA repair in uremic patients. Unscheduled DNA repair synthesis in peripheral lymphocytes was measured after both ultraviolet (UV) and gamma irradiations. In hemodialysis (HD) patients the repairs were normal, but in chronic renal failure (CRF) patients not yet on dialysis treatment, both UV- and gamma-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 26 publications
4
27
0
1
Order By: Relevance
“…Surprisingly, the short-term-hemodialysis groups of our study (less than 3 months and 3-12 months renal replacement therapy) even showed increased DNA repair compared with control subjects, while DNA repair of patients with medium-duration dialysis therapy (60 months) was comparable to controls. These latter data fit well to similar results from Israel in MHD patients treated for an average of 45 months [91,92]. In contrast, in patients with nondialyzed chronic renal failure, decreased DNA repair was found [92].…”
Section: Impaired Dna Repair After Long-term Hemodialysis Treatmentsupporting
confidence: 78%
“…Surprisingly, the short-term-hemodialysis groups of our study (less than 3 months and 3-12 months renal replacement therapy) even showed increased DNA repair compared with control subjects, while DNA repair of patients with medium-duration dialysis therapy (60 months) was comparable to controls. These latter data fit well to similar results from Israel in MHD patients treated for an average of 45 months [91,92]. In contrast, in patients with nondialyzed chronic renal failure, decreased DNA repair was found [92].…”
Section: Impaired Dna Repair After Long-term Hemodialysis Treatmentsupporting
confidence: 78%
“…The complication of clonal emergence may increase the chance that a clinically silent primary or controllable/reversible secondary hyperplasia becomes a clinically important disease that requires surgery. It is also possible that an impaired capacity for DNA repair, which has been described in uremic patients (32,33), further increases the likelihood of clonal transformation in their parathyroid glands.…”
Section: Dna Sample Preparationmentioning
confidence: 99%
“…It is of note that UV irradiation-induced DNA repair in PBMC exhibited a similar pattern, i.e. DNA repair increased significantly following HD [7, 8]. …”
Section: Discussionmentioning
confidence: 97%